An overview: can molecular gastronomy and gastropyhsic influence in food design for the elderly in Malaysia? / Farhan Faat … [et al.] - Faat, Farhan; Ramli, Rafidah Aida; Che Amat, Nur'Hidayah; Badiuzaman, Ahmad Fauzan; Mohd Zahari, Mohd Salehuddin (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Malaysia is a developing nation with a rapidly aging population is widely acknowledged. Dysphagia, or trouble swallowing and digesting, is becoming more common as the population ages. It is important to emphasize that people who have dysphagia need nutrient-rich foods with the right texture to help with intake and to provide the necessary nutrients. As technology advances and becomes more sophisticated in practically every aspect, gastronomy in food and cooking is not left behind in assisting the elderly. The development of molecular gastronomy and gastropyhsic knowledge may be able to improve the nutritional and feeding quality of life for elderly individuals. Due to the dearth of knowledge on molecular gastronomy and gastrophysics in Malaysia, this study able to add to the body of knowledge and provide useful information. This study will be carried out to investigate the impact of hedonic qualities and acceptance of inspired food products on the elderly.